2022
DOI: 10.1111/pbi.13960
|View full text |Cite
|
Sign up to set email alerts
|

Bt maize can provide non‐chemical pest control and enhance food safety in China

Abstract: Summary China is the world's second‐largest maize producer and consumer. In recent years, the invasive fall armyworm Spodoptera frugiperda (J.E. Smith) has adversely affected maize productivity and compromised food security. To mitigate pest‐inflicted food shortages, China's Government issued biosafety certificates for two genetically modified (GM) Bt maize hybrids, Bt‐Cry1Ab DBN9936 and Bt‐Cry1Ab/Cry2Aj Ruifeng 125, in 2019. Here, we quantitatively assess the impact of both Bt maize hybrids on pest feeding da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…We suspect that area-wide adaptation of such Bt maize would reduce H. armigera infestation across the growing season, both in maize and in various spring and summer crops the following year. To delay the evolution of Bt resistance in H. armigera, refuges of non-Bt maize should be planned and required, given that the other crops that are hosts for H. armigera produce only a few overwintering individuals (Li et al, 2020b;Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that area-wide adaptation of such Bt maize would reduce H. armigera infestation across the growing season, both in maize and in various spring and summer crops the following year. To delay the evolution of Bt resistance in H. armigera, refuges of non-Bt maize should be planned and required, given that the other crops that are hosts for H. armigera produce only a few overwintering individuals (Li et al, 2020b;Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…69 The commercial cultivation of genetically modified (GM) Bacillus thuringiensis (Bt) crop varieties is a core constituent of IPM, e.g., suppressing the population of herbivorous pests, reducing pesticide use, and improving the ecology of crop fields. [71][72][73] Since 2002, the Bt corn events MON810 and Bt11 (expressing Cry1Ab protein) have been approved for commercial cultivation in Philippines and Vietnam, which proved to be effective against ACB, and drastically reduced leave injury and borer tunnels by 84-99%. 74,75 Moreover, the ACB populations in this area still remain susceptible to Bt corn hybrids containing Cry1Ab toxin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the deeper commercialization of Bt corn and Bt soybean in China will pose a challenge to the natural refuge strategy of the cotton bollworm [ 86 ]. Small-scale experiments have shown that the control effect of transgenic insect-resistant corn on the fall armyworm ( Spodoptera frugiperda) could reach 95%, and the yield could increase by 6.7–10.7%, thus greatly reducing the cost of pest control [ 87 ]. The increase in yield and reduction in control costs may attract a large number of Chinese farmers to widely plant related varieties.…”
Section: Challenges and Directions Of Cotton Pest Resistance Manageme...mentioning
confidence: 99%